Respect With Recognition? A Defence of the OCSTA’s “Respecting Difference” Policy - Jordan, Michael Robert (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2016)
Philosopher Lauren Bialystok argues that some of the ideas within Ontario’s Catholic trustees’ document entitled ‘Respecting Difference’ fail to respect homosexual Catholic schoolchildren. I argue that Bialystok’s argument is unsuccessful because she begs at least three questions.